Epidemiological and Economic Evaluation of Alternative On-Farm Management Scenarios for Ovine Footrot in Switzerland - Zingg, Dana; Steinbach, Sandro; Kuhlgatz, Christian; Rediger, Matthias; Schüpbach-Regula, Gertraud; Aepli, Matteo; Grøneng, Gry M.; Dürr, Salome (Frontiers in Veterinary Science, 2017)
Footrot is a multifactorial infectious disease mostly affecting sheep, caused by the bacteria Dichelobacter nodosus. It causes painful feet lesions resulting in animal welfare issues, weight loss and reduced wool production which leads to a considerable economic burden in animal production. In Switzerland, the disease is endemic and mandatory coordinated control programs exist only in parts of the country. This study aimed to compare two nationwide control strategies and a no intervention scenario with the current situation, and to quantify their net economic effect. This was done by sequential application of a maximum entropy model (MEM), epidemiological simulation and calculation of net economic effect using the net present value method. Building upon data from a questionnaire, the MEM revealed a nationwide footrot prevalence of 40.2%. Regional prevalence values were used as inputs for the epidemiological model. Under the application of the nationwide coordinated control program without (scenario B) and with (scenario C) improved diagnostics (PCR test), the Swiss-wide prevalence decreased within 10 years to 14% and 5%, respectively. Contrary, an increase to 48% prevalence was observed when terminating the current control strategies (scenario D). Management costs included labor and material costs. Management benefits included reduction of fattening time and improved animal welfare, which is valued by Swiss consumers and therefore reduces societal costs. The net economic effect of the alternative scenarios B and C was positive, the one of scenario D negative and over a period of 17 years quantified at CHF 422.3, 538.3 and -172.3 million (1 CHF = 1.040 US$), respectively. This implies that a systematic Swiss-wide management program under the application of the PCR diagnostic test is the most recommendable strategy for a cost-effective control of footrot in Switzerland.